MAṢLAḤAH, TRANSPARENCY, AND ASSET PROTECTION: A STUDY OF INVESTOR PROTECTION IN THE ISLAMIC CAPITAL MARKET WITHIN CONTEMPORARY SHARIA FINANCIAL FATWAS - Muhammad Fahmi Ardian; Akhmad Muhaini; Achmad Nursobah; M. Fijar Ishlahul Ummah (al-Mawarid Jurnal Syariah dan Hukum (JSYH), 2026)
Purpose - This study aims to analyze the construction and application of the principles of maṣlaḥah, transparency, and asset protection in contemporary Islamic finance fatwas, with a focus on DSN-MUI Fatwa No. 157/DSN-MUI/A/IU/2024 regarding the protection of investor assets in the Islamic capital market. This study evaluates how the limits of maṣlaḥah according to Sheikh Said Ramadhan al-Bûthî are operationalized within the normative framework of fatwas, as well as their implications for strengthening the principles of transparency and investor protection. Methods - This research is a literature review employing a descriptive-analytical approach. The primary sources consist of the text of DSN-MUI Fatwa No. 157/DSN-MUI/A/IU/2024 and the work of al -Bûthî, namely “Dhawâbith al-Maslahah fi al-Syari‘ah al-Islamiyyah,” which are analyzed based on the five parameters of maṣlaḥah and the principle of ḥifẓ al-māl within the framework of the maqashid al-shari‘ah. Findings - DSN-MUI Fatwa No. This is reflected in regulations that emphasize the segregation and protection of investor assets, the strengthening of transparency principles in fund management, and oversight of potential deviations. This fatwa explicitly closes loopholes in practices leading to usury (riba), uncertainty (gharar), market manipulation, and other forms of injustice toward investors. This fatwa explicitly closes loopholes in practices leading to usury (riba), uncertainty (gharar), market manipulation, and other forms of injustice toward investors. The principle of ḥifẓ al-māl (protection of wealth) serves not only as a normative goal but also functions as an ethical and legal foundation for building an accountable and sustainable asset protection system. These findings indicate a shift from a normative approach toward a more applied approach in the formulation of contemporary Islamic financial fatwas. Contribution/limitations - This study bridges the gap between classical maṣlaḥah theory and modern financial practices. However, it remains normative in nature and has not yet been empirically tested. Originality - This study offers an original perspective on understanding the relevance of classical thought as a moral and legal foundation for strengthening the Islamic capital market system.